Effect of Community Size on Eligibility for Early Intervention for Infants With a Neonatal Intensive Care Experience. Issue 3 (15th December 2013) - Roberts, Holly; Needelman, Howard; Jackson, Barbara; McMorris, Carol; Munyon, Abbey
Abstract Purpose To determine if population density (rural vs urban) in a child's home community influenced the decision of eligibility for early intervention (EI) services. Methods The sample included 356 infants with a gestational age of <31 weeks referred from a statewide child find program for an evaluation for EI services. A binary logistic regression analysis was completed to determine which variables predicted acceptance into EI services. Findings Infants less than 31 weeks gestation residing in rural areas were more likely to be eligible for EI services than premature infants (ie, <31 weeks gestation) with similar birth characteristics from urban areas. A binary logistic regression analysis revealed an odds ratio for eligibility for EI services among children living in rural areas compared to those living in urban areas was 3.007 (95% CI, 1.497 to 6.040). Additionally, the odds ratio for eligibility for males as compared to females was 1.908 (95% CI, 1.017 to 3.578). Participants who lived in a rural area and were male were more likely to be eligible for EI services than those who lived in urban locations and were female. Conclusions Factors such as community support, experience with high‐risk populations, and differences in interpreting eligibility criteria may influence the differences found between the rural and urban populations. Analysis of intervention cost versus effectiveness will be needed to determine whether the system as adopted in the rural versus urban environment is more appropriate for the provision of EI services.